Study on Brewing Quality of Sorghum (Sorghum bicolor, L. Monech) - Acharya, Dev Raj; Shrestha, Rabin; Thapa, Santosh (Journal of Food Science and Technology Nepal, 2024)
With an aim to bring a variation in quality as well as to reduce the cost of beer, sorghum malt has also gained popularity and thus this study is focused on studying the suitability of sorghum in beer making. Sorghum was malted and different proportions of the malt were mixed with commercial barley malt to produce beer. Germination for 3 days yielded the highest amylase activity in sorghum. Sorghum malt was significantly different (p<0.05) from commercial barley malt in moisture, starch content, reducing sugar, protein, % extraction, specific gravity and amylase activity. The proportion of sorghum malt used along barley malt altered the TSS, viscosity, pH and specific gravity of wort significantly (p<0.05). Increasing the proportion of sorghum malt resulted in an increase in TSS, pH, ash content, dextrin, acidities, methanol content and tannin content whereas there was a decrease in apparent extract, total reducing sugars and alcohol content of the beers produced. The beer made out of sorghum malt: barley malt (25:75) was found superior to other formulations as well as to barley malt beer both in terms of chemical and sensory properties. Sorghum malt: barley malt (25:75) beer differed significantly (p<0.05) from market beer in terms of TSS, real extract %, starch content, ash content, acidity, alcohol content, methanol content and fusel oil content while pH, color, viscosity, original extract %, apparent extract %, real degree of fermentation, reducing sugar, protein, tannin, specific gravity, total aldehyde and ester content were statistically similar. Likewise, sorghum malt: barley malt (25:75) beer had significantly different (p<0.05) appearance and clarity, color, flavor and overall acceptance while the mouthfeel was similar to market bought beer.